Referral of patients for pre‐implantation genetic diagnosis: A survey of obstetricians. (9th September 2016) - Morrow, April; Seeho, Sean; Barlow‐Stewart, Kristine; Fleming, Jane; Meiser, Bettina; Karatas, Janan
Abstract : Background: Pre‐implantation genetic diagnosis (PGD) is a molecular diagnostic technique in which embryos are tested for specific genetic abnormalities to enable the selection of those unaffected by the condition. Previous Australian evidence suggested that women who are not informed about PGD by their obstetrician feel disempowered about not being given this option. Aims: This study aimed to explore obstetrician knowledge regarding PGD and identify barriers to referral. Materials and methods: An invitation to the study with a link to an online questionnaire was e‐mailed by the Royal Australian and New Zealand College of Obstetricians and Gynaecologists to their members. Results: In total, 372 practising obstetricians responded. Perceptions of their patients' financial status and ability to access PGD were identified as barriers to referral. There was variability in referral for PGD and/or genetic services according to the clinical scenario and in the perceived appropriateness of PGD for different indications. Obstetricians who had undergone professional development related to PGD were more likely to discuss PGD than those who had not (χ 2 = 6.44; P < 0.01). Conclusions: The results highlight the need for additional training, development of educational resources and awareness of appropriate referral pathways to ensure that those couples who are eligible for PGD are informed.